2018
DOI: 10.1002/admi.201701296
|View full text |Cite
|
Sign up to set email alerts
|

Lubricin Antiadhesive Coatings Exhibit Size‐Selective Transport Properties that Inhibit Biofouling of Electrode Surfaces with Minimal Loss in Electrochemical Activity

Abstract: Electrochemical sensing is a highly effective technique for rapidly detecting and quantifying the presence of electroactive compounds in solution. However, effective sensing requires the electrode surface to be free of contamination, which makes this technique particularly susceptible to the effects of surface fouling due to the unwanted adhesion of biomolecules. Unfortunately, coating electrodes with antiadhesive molecules typically causes electrical passivation with detrimental effects upon electrochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 37 publications
5
62
0
Order By: Relevance
“…Thus as expected, the amount of LUB immobilized on the Pt electrode surfaces increased in accordance with Pt exposure to increasing concentrations of LUB in solution. The LUB surface coverage levels obtained for Pt surfaces in this study are at least one order of magnitude higher than LUB surface coverages reported on Au surfaces . This was confirmed by performing the chronocoulometric experiments using Au electrodes (Supplementary information Figure S2).…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…Thus as expected, the amount of LUB immobilized on the Pt electrode surfaces increased in accordance with Pt exposure to increasing concentrations of LUB in solution. The LUB surface coverage levels obtained for Pt surfaces in this study are at least one order of magnitude higher than LUB surface coverages reported on Au surfaces . This was confirmed by performing the chronocoulometric experiments using Au electrodes (Supplementary information Figure S2).…”
Section: Methodssupporting
confidence: 77%
“…The direct immobilization of LUB layers on surfaces has been investigated on different surfaces such as negatively charged mica, silica, polymermeric microfluidic devices, and more recently gold ,. The antifouling properties of LUB tethered to gold surfaces has also been studied electrochemically and it was shown that the LUB (native and recombinant) coatings were of sufficiently low impedance that Faradaic electrochemistry still occurred at the underlying electrodes whilst still preventing biofouling by large molecules such as bovine serum albumin . Despite these documented reports of the impressive antifouling properties of LUB, studies towards bionic implants applications are yet to be conducted.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a self‐assembled lubricin based antiadhesive and antifouling coating was utilized as permselective surface for the small electroactive compounds. Its size selectivity lies in the telechelic brush structure transport that just allows the small size molecule to pass to transducer surface .…”
Section: Modified Electrodes Based On Permselective Coatings For Biommentioning
confidence: 58%
“…The assembling structure of the coating prominently controls the selectivity of the membrane. The more ordered packing of the polymer structure leads higher permselectivity with very low permeability . The electrosynthesized coatings simplify the immunoassay by providing the direct exposure of the biosensor to the unprocessed complex matrix material .…”
Section: Modified Electrodes Based On Permselective Coatings For Biommentioning
confidence: 99%
“…Consequently, protein‐resistant coatings may resist bacterial attachment and biofilm formation. Many authors use the level of protein adsorbed on a surface as a measurement tool to predict fouling . Furthermore, it is widely recognized that proteins are the main components of biofouling .…”
Section: Resultsmentioning
confidence: 99%